The Budd-Chiari syndrome : a study of diagnosis, haemodynamics and treatment - Clain, David Jocelyn (UCT/MRC Liver Research Centre, 2017)
Symptomatic occlusion of the hepatic veins is a rare condition caused by tumour or thrombus arising either locally or by extension from the inferior vena cava. It is usually called the Budd-Chiari syndrome. The etiology remains unknown in over two-thirds of the patients. Its rarity and interest has led to a large number of individual case reports. 322 instances of symptomatic hepatic vein occlusion have been reported, of which 184 are single case publications. There are only six series of more than five cases (Nishikawa, 1910; Corinini and Oberson. 1937; Palnar, 1954; Parker, 1959; Gibson, 1960; Safouh and Shehata, 1965) and these have been largely drawn from autopsy records, although Palmer (1954) described seven patients seen during life. The clinical and pathological features of hepatic vein occlusion have been described in a number of papers (Hess, 1905; Thompson and Turnbull, 1912; Armstrong and Carnes, 1944; Kelsey and Comfort, 1945; Thompson, 1947; Parker, 1959; Gibson, 1960) during the one hundred and twenty years since the publication of Budd's treatise. However, accurate diagnosis has generally relied on autopsy, and detailed investigations have seldom been performed. Consequently, little is known of the roentgenographic and haemodynamic features. The diagnosis of liver disease has been revolutionized by such special techniques as percutaneous liver biopsy, portal pressure measurements, isotope scanning and selective arteriography and venography. This study describes six patients with the Budd-Chiari syndrome in whom these methods have been applied to establish the diagnosis, to ascertain the underlying cause and to assess the possibility of surgical intervention. Special attention has been given to hepatic venography and hepatography. The vascular pattern in the Budd-Chiari syndrome has been compared with that in normals and in patients with other diseases of the liver. Diagnostic features have been determined and an attempt made to evaluate compensatory changes in the lymphatic drainage and venous blood supply following hepatic vein obstruction. Alterations in portal dynamics have also been recorded. The clinical course has been followed and the effect of treatment assessed in each patient. Finally, the literature has been reviewed with particular reference to the diagnosis and treatment of hepatic vein thrombosis. The studies reported in this thesis were carried out during the tenure of a Research Fellowship in the Royal Free Hospital School of Medicine, and they were supported by a grant from the William Shepherd Bequest to the Royal Free Hospital. The special radiological procedures, haemodynamic studies, isotope investigations and laboratory work were personally performed with the exception of the scintillation scans, coeliac axis arteriograms and the other individual tests acknowledged overleaf.